PENGADAAN PERALATAN PENUNJANG PRODUKSI GERIT DI DUSUN PETUNGSEWU KECAMATAN TUMPANG KABUPATEN MALANG - Mahmudatul Himma; Diana Eka Poernamawati; Achmad Suyono; Tri Wahyu Widodo; Esther Hesline Palandi (P3M Politeknik Negeri Malang, 2023)
The community in Dusun Petungsewu, Duwet Village, Tumpang District, Malang Regency is a producer of corn rice (gerit). So far, the production process is carried out using manual equipment. Where for the corn milling process (slep) is carried out in the market. Then the process of separating the slep from the feces is done manually using a tampah (nampeni). Therefore, this community service activity aims to increase the production capacity of gerit through the procurement of a gerit sieving machine. It also makes the production process more continuous. This activity is in the form of providing a sifter and woven bamboo machine for drying to the MSME partners of Polinema and providing assistance on how to operate the production equipment to partners. In addition, the program is expected to provide positive benefits for gerit producers. Procurement of sifting machine can increase the productivity of gerit producers. In addition, the results of sieving using a sieving machine have increased compared to conventional methods. By using this machine, less power is needed and can shorten the time to sieve the gerit.